Developing assessment instruments of debate practice in Indonesian Language learning - Septiana Farida; Farida Agus Setiawati (REID (Research and Evaluation in Education), 2021)
This study aims to develop an instrument for assessing debate practice in Indonesian Class X senior high school (Sekolah Menengah Atas or SMA/Madrasah Aliyah or MA) learning. The theoretical construct of the instrument was found after reviewing several theories, including speaking skills that apply to debate practice, especially those based on the Australian Debating Federation. The non-test instrument development procedure used is the Mardapi model, which includes non-cognitive. Ten material experts reviewed the draft instrument (two lecturers and eight Indonesian Language Teachers Class X in the SMA/MA in Yogyakarta Special Region) then it was calculated using the Aiken formula to prove the validity of the contents of the instrument. The draft instrument was also tested by two raters/evaluators to assess the debate practice. The results of this trial were used to calculate inter-rater reliability using Cohen Kappa. The assessment instrument was declared reliable from the calculation of the inter-rater reliability value of the Kappa formula, which was obtained at 0.678. The final item number of the instrument after the exploratory factor analysis is 33 items with adjustments to the composition of the dimensions of the statement items.